Are Medical Students and Interns at Risk of Acquiring Methicillin Resistant Staphylococcus Aureus (MRSA)? - Christy Vijay; Pretesh R Kiran; Savitha Nagaraj; N S Srikanth; Rajitha K (Medsci Publications, 2016)
Introduction: MRSA is conventionally considered as a nosocomial pathogen (though of late it is seen in the community). It is a pathogen which can infect patients and be carried innocuously, most commonly on the hands and for a longer duration in the anterior nares. This study was done on Medical Students and Interns in a medical college in India to check if they colonised with MRSA.. The risk factors among the subjects were found to be low. Objectives: This study was aimed at finding the prevalence of Nasal carriers of MRSA and contributing risk factors among Medical Students and Interns. Methods: This was a cross sectional study. The study group included medical students and interns above the age of 18 years. The study involved 150 medical students and interns. The students who participated in the study were 30 each from the first year to interns. Results: One subject was found to be positive for MRSA. Conclusion: From the study it was concluded that the prevalence of MRSA among medical students was low. It was also noticed that students were aware of the need for good hygiene practices.